Radiographic studies of the hyoid bone and cervical spine in Angle Class I and Class II/2nd Division malocclusions - Ana Lucia de Oliveira NASCIMENTO; Fabiano REIS; Mirian Hideko NAGAE (Universidade Estadual Paulista, 2022)
Abstract Introduction Interdisciplinary investigative study of the stomatognathic-cervical complex, necessary to understand the structure and biomechanics of the hyoid bone and cervical spine in Class I and II / 2nd Division participants. Objective To analyze the position of the hyoid bone and the curvature of the cervical spine on lateral radiographs of participants with Class I and II/2nd Division Angle malocclusion. Material and method We evaluated the position of the hyoid bone from its alignment with the corresponding cervical vertebra. The presentation of curvature of the cervical spine was evaluated from the fourth cervical vertebra. Result There was a statistically significant difference in the position of the hyoid bone (p=0.027) between the classes, which was located at C3 in Class I and further down, between C3 and C5, in Class II/2nd Division. The cervical spine showed alterations in both classes, with an increase, rectification, and inversion of the curvature with no statistical difference between them (p=0.533). Conclusion In this study, the hyoid bone showed different positions in the malocclusions studied, however, poor posture of the cervical spine was common in both classes.